T‐cell responses and therapies against SARS‐CoV‐2 infection - Salman M. Toor (8854751) (2023)
Coronavirus disease 2019 (COVID-19) is caused by SARS-CoV-2, a novel coronavirus strain. Some studies suggest that COVID-19 could be an immune-related disease, and failure of effective immune responses in initial stages of viral infection could contribute to systemic inflammation and tissue damage, leading to worse disease outcomes. T cells can act as a double-edge sword with both pro- and anti-roles in the progression of COVID-19. Thus, better understanding of their roles in immune responses to SARS-CoV-2 infection is crucial. T cells primarily react to the spike protein on the coronavirus to initiate antiviral immunity; however, T-cell responses can be suboptimal, impaired or excessive in severe COVID-19 patients. This review focuses on the multifaceted roles of T cells in COVID-19 pathogenesis and rationalizes their significance in eliciting appropriate antiviral immune responses in COVID-19 patients and unexposed individuals. In addition, we summarize the potential therapeutic approaches related to T cells to treat COVID-19 patients. These include adoptive T-cell therapies, vaccines activating T-cell responses, recombinant cytokines, Th1 activators and Th17 blockers, and potential utilization of immune checkpoint inhibitors alone or in combination with anti-inflammatory drugs to improve antiviral T-cell responses against SARS-CoV-2. Other Information Published in: Immunology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1111/imm.13262